TEQUILA: MAGICAL CENTER, TRADITIONAL TOWN. HERITAGE OR PRIVATIZATION? (Andamios, Revista de Investigación Social, 2009)
This paper discusses whether the distinctions granted by international organizations -and also by certain public policies- which ad value to some areas in ordinary towns; really trigger the promotion of values, traditions, environment preservation, regional development and social participation. Through the analytical readings of the cultural landscape of Tequila’s historical downtown, in Jalisco Mexico, we can notice the transformation of specific perimeters of a town similar to many others in Latin America, which gradually -and due to the economical and political intervention of both international organisms and the Mexican government- has turned from a rural area into an important tourist destination in Western Mexico and a referent in the construction of a new national identity, linked to successful commodities within the context of globalization.
Keywords: Tequila; landscape; heritage; cosmetic politics